Staphylococcus lugdunensis Endocarditis Complicated by Embolism in an 18-Year-Old Woman with Mitral Valve Prolapse. (29th January 2013) - Pecoraro, Rosaria; Tuttolomondo, Antonino; Parrinello, Gaspare; Pinto, Antonio; Licata, Giuseppe
Abstract : Staphylococcus lugdunensis is a coagulase-negative staphylococcus (CNS). It is a major cause of prosthetic valve endocarditis; mitral valve prolapse (MVP) has emerged as a prominent predisposing structural cardiac abnormality. We describe a case of Staphylococcus lugdunensis endocarditis in an 18-year-old woman with preexisting mitral valve prolapse complaining of fever, a one-month history of continuous-remittent fever (T max 38.6°C). The transthoracic echocardiogram revealed large vegetation on the anterior mitral valve leaflet flopping from the atrial side to the ventricular side. Five sets of blood cultures were positive for coagulase-negative staphylococci. During hospitalization, after two weeks of antibiotic therapy, the patient complained of sudden pain in her right leg associated with numbness. Lower limb arterial Doppler ultrasound showed an arterial thrombosis of right common iliac artery. Transfemoral iliac embolectomy was promptly performed and on septic embolus S. lugdunensis with the same antibiotic sensitivity and the same MIC values was again isolated. Our patient underwent cardiac surgery: triangular resection of the A2 with removal of infected tissue including vegetation. Our case is an example of infective endocarditis by S. lugdunensis on native mitral valve in a young woman of 18 with anamnesis valve prolapse.